Pertumbuhan dan Perkembangan Otak Fetus Mencit Setelah Induksi Ochratoxin A Selama Periode Organogenesis - Arum Setiawan; Mammed Sagi; Widya Asmara; Istriyati Istriyati (Jurusan Biologi FMIPA Universitas Cenderawasih, 2013)
This experiment was performed to examine the effects of Ochratoxin A (OTA) during organogenesis period on fetuses brain growth and development. Thirty pregnant mice were divided randomly into 5 groups of 6. Ochratoxin A was dissolved in sodium bicarbonate and administered orally on seventh to fourteenth days of gestation at dosage of 0.5, 1.0, 1.5 mg/kg bw, respectively. The remaining animals were used as an untreated control, and placebo were given by Sodium Bicarbonate. At the age of 18-day pregnancy, mice were sacrified dan taken its brains. The fetuses brain growth and development were observed by measure brain weight, cereberum width and length, cerebellum width and length, and the wall thichkness of cerebrum. Result of this studies indicated that OTA caused decreased of brain weight, the length and width of cerebrum and cerebellum, the wall thickness of cerebrum significantly.Key words: Ochratoxin A, brain, cerebrum, cerebellum, mice.